Sistem Informasi Pengolahan Data Siswa Berbasis Web Pada SMK Asga Mandiri Menggunakan Metode Waterfall - Adjie Taruna Surya; Yulia Agustina Dalimunthe; Arie Rafika Dewi (LKP Unity Academy, 2023)
The development of technology in the current era of globalization is moving very rapidly and the information circulating is increasingly complex so that the world of education must be able to follow the development of special technology in the field of computer technology, along with current technological developments. SMK Asga Mandiri is an educational institution in charge of handling activities related to education, the main purpose of which we know to educate the nation's life. The operator of SMK Asga Mandiri to manage student data, department data, teacher data, and alumni data is still manual and data storage is still compiled manually such as archives or documents. Data that could manually result in loss, damage, or burning. Therefore, this web-based student data management information system is considered very necessary to provide convenience to the special school SMK Asga Mandiri. Based on the background above, the researcher proposed the title